Are the Effects of Minimum Wage Increases Always Small? A Reanalysis of Sabia, Burkhauser, and Hansen. (March 2016) - Hoffman, Saul D.
In a 2012 article, Sabia, Burkhauser, and Hansen reported very large negative effects of the 2004 to 2006 increase in the New York State minimum wage on the employment of young, less-educated workers. Hoffman reexamines their estimates using data from the full Current Population Survey (CPS), rather than the smaller CPS-MORG files they used, and finds no evidence of a negative employment impact. The full CPS, which is the source of U.S. official labor market statistics, is certainly the more appropriate and reliable data source. Furthermore, when Hoffman repeats the analysis using three states and the District of Columbia, which also had a substantial increase in the state minimum wage in the same time period, he finds evidence of a small positive employment effect. Together, the two findings are consistent with other, more recent research that reports very weak or zero employment effects of the minimum wage.